PENINGKATAN KEMAMPUAN GURU DALAM MERANCANG DIGITAL MIND MAP DENGAN MINDMAPLE - Sulistio, Prayogo Hadi (Jurnal Pengabdian Masyarakat AbdiMas, 2017)
AbstractTraditional teaching which is based on the teachersâ explanation using cupboard causes students less interest to learn. This condition is also triggered by low competence of teachers to create ICT-based interactive media to help them teaching in the classroom. So that, this community service is aimed to increase teachersâ competence to develop learning materials based on digital mind map in the classroom of SD Pelita 2. The method used in this community service is active and participatory learning which includes explanation, discussion, demonstration, presentation and consultation. Explanation and discussion are aimed to give explanation about digital mind map using Mindmaple. Demonstration is done when teachers develop the sample of digital mind map adopting learning media they want to teach using Mindmaple. Presentation is done after teachers were finished to create the interactive leaning media. Consultation is done when the teachers want to adopt their learning materials to create interactive learning media using Mindmaple and at the end to be implemented in real classroom context. It is found that the community service gave positive impact in increasing teachersâ competence to use ICT-based learning media especially in creating digital mind map using Mindmaple and creating pleasant learning situation for the students so that they do not get easily bored.Â Keywords: learning media development, digital mind map, mindmaple aplicationÂ AbstrakÂ Pengajaran tradisional yang berbasis kepada penjelasan guru menggunakan papan tulis menyebabkan para siswa kurang tertarik untuk belajar. Kondisi ini juga disebabkan oleh rendahnya kompetensi guru untuk menciptakan media interaktif berbasis komputer untuk membantu mereka untuk mengajar di kelas. Oleh karena itu, kegiatan pengabdian masyarakat ini ditujukan untuk meningkatkan kompetensi guru untuk mengembangkan materi pembelajaran berbasis digital mind map menggunakan Mindmaple di kelas SD Pelita 2. Metode yang digunakan dalam pengabdian masyarakat ini adalah active dan participatory learning yang meliputi ceramah, diskusi, demonstrasi, presentasi dan konsultasi. Ceramah dan diskusi ditujukan untuk menjelaskan tentang digital mind map menggunakan Mindmaple. Presentasi dilakukan setelah guru selesai menciptakan media pembelajaran interaktif. Konsultasi dilakukan ketika guru ingin mengadopsi materi ajar untuk mencipkan media pembelajran interaktif menggunakan Mindmaple dan pada akhirnya media ajar tersebut digunakan di konteks kelas sesungguhnya. Kegiatan pengabdian masyarakat ini memberikan pengaruh positif dalam meningkatkan kompetensi guru untuk menggunakan media pembelajaran berbasis ICT dalam membuat digital mind map menggunakan Mindmaple dan menciptakan suasana belajar yang menyenangkan bagi siswa sehingga mereka tidak mudah bosan.Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Kata Kunci: pengembangan media pembelajaran, digital mind map, aplikasi mindmaple